Accuracy of self-perceived risk of falls among hospitalised adults in China: an observational study - Wei Zhang; Lin Zhu; Jingfen Jin; Guanjun Bao; Yuanfei Liu; Ye Luo (BMJ Open)
Objective To evaluate the accuracy of self-perceived risk of falls in hospitalised adults and explore factors associated with the differences.Design Cross-sectional study.Setting We conducted the study in two tertiary general hospitals located in Zhejiang province and Shandong province in China.Participants 339 patients were recruited using convenient sampling. The majority of them were men (54%), aged 61–70 (40.1%) and had received secondary school education or lower (82%).Outcome measures The Fall Risk Perception Questionnaire and the Morse Fall Scale (MFS) were used to measure patients’ self-perceived risk of falls and nurses’ assessment. Other risk factors of falls were assessed to identify the determinants of disparities.Results Most patients (74.6%) had a high risk of falls according to MFS. Only 61.9% of the patients’ perceived risk matched with the assessment of nurses. Nearly one-third (27.5%) underestimated their fall risk, while the remaining (10.6%) overestimated. Multivariable logistic regression analyses revealed that older age, lower number of comorbidities, not having fear of falling and emergency department were the significant factors associated with underestimated risk of falls (p<0.05). Besides, endocrine department and having fall-related injuries were significantly associated with overestimated risk of falls (p<0.05).Conclusion Hospitalised patients were proven to be poor at recognising their risk of falls. Measurement of patients’ self-perceived and health professionals’ assessment of fall risk should be conducted to evaluate the disparity. This study provides a solid foundation to raise medical staff’s awareness of the targeted population, identify the underlying factors and implement tailored fall prevention strategies and education.